Artificial Intelligence (AI) on Learning Process - Shaun Kim Sopera; John Stephen Alaban; Zaira Briones; Nicko A. Magnaye (MultiTech Publisher, 2023)
Artificial intelligence (AI) is a helpful technology. By providing college students with more individualized and productive learning environments, they support education. This research examines how artificial intelligence (AI) works in education and enhances teaching and learning results for Mindoro State University students and teachers. The study will survey students and instructors to gauge their perspectives on AI, assess its benefits and obstacles in education, and propose strategies for successfully implementing AI into teaching and learning techniques. The poll will ask students about their understanding of AI and their experiences using AI-powered learning tools. According to the results of this study, students and teachers at the University have a strong belief and a positive outlook on the potential of AI to significantly improve the learning journey and outcomes for both students and instructors, as evidenced by the weighted mean rating of 4.37 for all categories combined. Overall, respondents strongly agree that artificial intelligence has the potential to considerably improve student and instructor learning and teaching outcomes at the University, as indicated by the average mean score of 4.23, which is characterized as